Cardiovascular diseases morbidity and mortality among children, adolescents and young adults with dialysis therapy - Li, Lung-Chih; Tain, You-Lin; Kuo, Hsiao-Ching; Hsu, Chien-Ning (Frontiers in Public Health, 2023)
Background The age-specific burden of cardiovascular disease (CVD) and mortality in pediatric and young adult patients with end-stage kidney disease (ESKD) remains unclear. We aimed to examine the prevalence and incidence of CVD and all-cause mortality in children and adolescents compared with adults with dialysis in Taiwan. Methods This retrospective observational cohort study comprised 3,910 patients with more than 2 time point receipts of dialysis therapy in a year, including 156 aged <12 years (children), 250 aged 13–20 years (adolescents), 1,036 aged 21–30 years (young adults) and 2,468 aged 31–40 years (adults) in a large healthcare delivery system in Taiwan (2003–2017). Age groups were classified by the date of first receipt of dialysis therapy. The outcomes include the composite of CVD events and any cause of death. Death-censored Cox proportional hazard models were used to evaluate the composite outcome risk of CVD in the four age groups. Results Among patients receiving dialysis treatment, the risk of composite CVD events [HR, 1.63 (1.22–2.19)] and mortality [HR, 1.76 (1.38–2.25)] was greater in children than the dialysis initiated in older patients. Non-atherosclerotic CVD was more prevalent, especially in younger patients, within the first 6 months after the initiation of dialysis. After 6 months of initial dialysis, the risk of atherosclerotic CVD was higher in adults than those for adolescents and children. The magnitude of CVD risk in adolescents who initiated dialysis therapy was higher in females [HR, 2.08 (1.50–2.88)] than in males [HR, 0.75 (0.52–1.10)]. Conclusion Younger patients undergoing chronic dialysis with a higher risk of CVD events than older patients are associated with a faster onset of non-atherosclerotic CVD and a higher risk of both CVD- and non-CVD-related mortality.